Sugar-sweetened beverages as risk factor of central obesity among women in reproductive age - Annisa, Nabila Rifka; Dieny, Fillah Fithra; Nissa, Choirun; Tsani, A. Fahmy Arif (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2020)
Background: Several risk factors for central obesity include high Sugar-sweetened Beverages (SSBs) intake, lack of physical activity, and lack of sleep duration. High fructose corn syrup, the sweetener used in SSBs, increase body weight because of the bad effect of insulin secretion and leptin release. The fructose from this beverage can increase visceral adiposity accumulation. Objectives: This study aimed to analyze the intake of Sugar-sweetened Beverages (SSBs), physical activity, and sleep duration as risk factors for central obesity among women in the reproductive AgeMethods: This study used case-control design consists of 38Subjects in case and control groups. All women were in childbearing age (20-29 years) selected using a simple random sampling technique. The data taken were weight, height, waist circumference, and hip circumference. Food intake and sugar-sweetened beverage intake were obtained by using Semi-Quantitative Food Frequency (SQ-FFQ) questionnaire. Physical activity data were obtained using the International Physical Activity Questionnaire (IPAQ) questionnaire. Sleep duration data were obtained using the Pittsburgh Sleep Quality Index (PSQI). Chi-Square test and logistic regression were used to analyze the data.Results: There were a significant relationship between Sugar Sweetened Beverages intake (p = 0.002, OR =5.926), energy intake of SSBs (p = 0.035, OR = 2.979) physical activity (p = 0.035, OR = 0.3111), duration of morning sleep / afternoon (p = 0.000; OR = 9.44) and sleep duration (p = 0.028, OR = 4.42) with central obesity. But there were no significant relationship between energy intake (p = 0.375), carbohydrates (p = 0.1), protein (p = 0.3), fat (p = 0.1) and fibers with central obesity.Conclusion: High intake of sugar-sweetened beverages, short duration of night's sleep and the duration>2 hours/day of a long day sleep are risk factors for increasing the incidence of central obesity among Women in reproductive Age.